Mobile e-services using HTML5 - Andersson, K.; Johansson, D. (2012 IEEE 37th Conference on Local Computer Networks Workshops, 2012)
New mobile networks and new devices like smartphones and tablets are rapidly changing opportunities for public sector units delivering smart, mobile e-services to their citizens. Moreover, the upcoming HTML5 standard allows for cross-device and cross-browser support making service development and deployment much more easier than before at lower costs. This paper analyzes the most important features of HTML5, CSS3, and WebGL and their applicability for mobile e-services in the public sector. Also, we present a novel architecture for mobile e-services using HTML5, mashups, and RESTful web APIs as important building blocks.